2021
DOI: 10.2147/ijgm.s339921
|View full text |Cite
|
Sign up to set email alerts
|

SLCO4A1 is a Prognosis-Associated Biomarker Involved in Neutrophil-Mediated Immunity in Thyroid Cancer

Abstract: Objective The study aimed to investigate the value of solute carrier organic anion transporter family member 4A1 (SLCO4A1) in thyroid cancer mainly from three aspects: expression, prognosis, and biological function analyses. Methods Based on various bioinformatic approaches, genes co-expressed with vascular endothelial growth factor C (VEGFC) in thyroid cancer were used for further survival and expression analyses to identify the target gene. After evaluation of the SLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…In addition, SLCO4A1 overexpression was associated with a shorter OS or DFS ( Figure 3 ). Interestingly, our results are similar to those of some studies, but the role of SLCO4A1 in the occurrence and development of COAD still needs to be further researched [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, SLCO4A1 overexpression was associated with a shorter OS or DFS ( Figure 3 ). Interestingly, our results are similar to those of some studies, but the role of SLCO4A1 in the occurrence and development of COAD still needs to be further researched [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that abnormalities of the SLCO4A1 gene have multifaceted 9 Mediators of Inflammation effects for many tumors. Overexpression of the SLCO4A1 gene in prostate cancer and thyroid cancer indicated a poor prognosis [48,50]. Buxhofer-Ausch et al have shown that SLCO4A1 may affect the accumulation of anticancer drugs in specific cancer cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Human β-defensin 1 (encoded by DEFB1) was found to be associated with Hp infection, while the mechanisms by which DEFB1 achieved its effects in GC remained unclear [49,50]. In contrast to our ndings, most studies indicated the elevated expression of SLCO4A1 might facilitate the progression of cancer, because they found that SLCO4A1 mediated the cellular uptake of many substrates including hormones, which regulated the progression of cancer through binding the hormone receptors [51][52][53]. It was possible that SLCO4A1 mediated the cellular uptake of estrone-sulfate and dehydroepiandrosteronesulfate in GC, which were the most important estrogen precursors in the plasma of postmenopausal females [53].…”
Section: Discussioncontrasting
confidence: 73%
“…It has been demonstrated that abnormalities in SLCO4A1 have diverse impacts on various tumors. Increased expression of SLCO4A1 in prostate and thyroid cancer has been associated with an unfavorable prognosis (28,29). A previous study indicated that SLCO4A1 may influence the accumulation of anticancer drugs in specific cancer cells, thereby exerting an antitumor effect (30).…”
Section: Discussionmentioning
confidence: 99%